Efek Moderasi Motivasi dan Masa Kerja Pada Pengaruh Stres Kerja Terhadap Perbedaan Kinerja Karyawan Pria Dengan Karyawan Wanita di Sekretariat BPK PENABUR Jakarta - Diana, Diana (Manajemen Bisnis Kompetensi, 2019)
The aim of this study was to analyze moderating effects of motivation and working period variables on the effect of work stress differences between male and female employees on employee performance at the Secretariat of BPK Penabur Jakarta. The approach of this study was quantitative to find out the role of motivation and working period in moderating the effect of work stress on employee performace. The population in this study was the BPK Penabur Jakarta employees with a total sample of 150 respondents. The analytical method used is a multiple linear regression method with interaction. Based ond the analysis conducted getting results for work stress is not significantly negative effect on employee perfomance. The motivation variable is very significant moderating the positive effect of work stress on employee performance. And the working period variable does not significantly moderate the negative effect of work stress on employee performance. The non-significant dummy variable shows that there are no differences in employee performance between male employees and female employees. Likewise there was no difference in work stress between male employees and female employees of BPK Penabur Jakarta.Keywords : work stress, moderating, motivation, working period, performance